Outcomes of Brand Image: A Conceptual Model - Mahadzirah, Mohamad; Wasib, Latif; Md. Aminul, Islam (2016)
The outcomes of brand image are denoted as the latent outputs of brand image on consumer response to the marketing of the brand. Organizations are well-known that brand image will build a competitive advantage in the market place that will increase their overall image with long-term sustainability. Indeed, current trends in modern marketing environment have changed extremely, and study of outcomes of brand image is increasingly becoming considerable to keep pace with this change. In this conceptual paper, we have summarized the literatures on currently prevailing concepts and approaches on brands that will allow us to identify the outcomes of brand image, and therefore will facilitate organizations to enhance their marketing efficiency and effectiveness. Based on a comprehensive review of several previous works, here we propose a plausible model for the outcomes of brand image in sequential order, namely, brand familiarity, customer satisfaction, brand trust and attitudinal loyalty of the brand.